(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the relationship of sentences with logical and grammatical categories. Logical categories can be expressed in a language by various means combinations of words, single words, affixes, intonation, etc., but they always get a corresponding expression in the language.